Emphysematous cystitis: a cause of hematuria post angioplasty. Issue 2 (19th February 2020) - Parker, Sidney; Bouayyad, Sarah; Tam, Jonathan; Kansal, Nisheeth; Bhattacharya, Vish
Abstract: Emphysematous cystitis (EC) is a rare, severe, urinary tract infection caused by gas-producing bacteria. It is characterized by the accumulation of air inside the bladder wall and/or lumen and is common among elderly diabetic females. This case of a 90-year-old female, who underwent bilateral iliac angioplasty and stenting, is the first published correlation between iliac angioplasty and the development of EC. The endovascular procedure performed was a success, but later on, she was confused and developed frank haematuria with a fall in haemoglobin levels. CT revealed severe EC with abundant gas tracking outside of urinary bladder into the extraperitoneal space. She was catheterized and empirical antibiotics were started and converted based on the culture sensitivities. Frequent follow-up ensured the resolution of a conservatively managed case. It is essential to increase the awareness of EC associated with angioplasties among the healthcare staff, particularly those undertaking vascular procedures.